Borehole seismic methods in high permeability sandstone - Almalki, Majed Ahmed (Curtin University, 2014)
In this research complex field borehole seismic measurements are made at a range of frequencies in weakly-consolidated, high-permeability sandstones. New 3D visualisation of phase velocity dispersion derived from multifrequency full waveforms reveals overlapping wave-modes in both open drill holes and sand-screened wells which appear to be sensitive to hydraulic permeability. Multidisciplinary studies of virtual source tomography, vertical seismic profiling and full waveform sonic provide credible information for understanding heterogeneous aquifers with complex sedimentary structures.